2017
DOI: 10.1136/annrheumdis-2017-212120
|View full text |Cite
|
Sign up to set email alerts
|

Scleroderma fibroblasts suppress angiogenesis via TGF-β/caveolin-1 dependent secretion of pigment epithelium-derived factor

Abstract: ObjectivesSystemic sclerosis (SSc) is characterised by tissue fibrosis and vasculopathy with defective angiogenesis. Transforming growth factor beta (TGF-β) plays a major role in tissue fibrosis, including downregulation of caveolin-1 (Cav-1); however, its role in defective angiogenesis is less clear. Pigment epithelium-derived factor (PEDF), a major antiangiogenic factor, is abundantly secreted by SSc fibroblasts. Here, we investigated the effect of TGF-β and Cav-1 on PEDF expression and the role of PEDF in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…Previous work has shown that SSc fibroblasts extracted from patient skin and cultured for an extended period still have enhanced Notch signalling and this is important for their profibrotic phenotype in vitro and for progression of tissue fibrosis in animal models 9 10. Evidence presented here shows that HOTAIR is an important epigenetic factor involved in maintaining Notch signalling through enhanced transcription of the receptor.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Previous work has shown that SSc fibroblasts extracted from patient skin and cultured for an extended period still have enhanced Notch signalling and this is important for their profibrotic phenotype in vitro and for progression of tissue fibrosis in animal models 9 10. Evidence presented here shows that HOTAIR is an important epigenetic factor involved in maintaining Notch signalling through enhanced transcription of the receptor.…”
Section: Discussionmentioning
confidence: 60%
“…In a complementary approach, we set out to induce stable overexpression of HOTAIR (or scrambled RNA) in human dermal fibroblasts immortalised through retroviral induced expression of HTERT as previously described 10. Immortalised dermal fibroblasts were infected with lentiviral particles carrying HOTAIR gene in frame with GFP and puromycin-resistance genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that microvascular endothelial dysfunction has as substrate the appearance of anti-endothelial antibodies and, mainly, the presence of anti-intercellular adhesion molecule (ICAM)-1 antibodies (6). Activated endothelial cells release proinflammatory cytokines and connective tissue growth factors, interleukin (IL)-1, IL-4, tumor necrosis factor (TNF)-α, IL-6 and IL-8 transforming growth factor (TGF)-β, which induce aberrant hyperactivated fibroblasts (7)(8)(9)(10)(11). Early endothelial cell involvement in SSc, leads to the destruction of blood capillaries with reduction in microvasculature through vascular repair and defective neoangiogenesis simultaneously with impaired lymphatic circulation followed by exudative accumulation and edema formation.…”
Section: Introductionmentioning
confidence: 99%
“…a-2-Antiplasmin specifically induces TGFb1 production during the process of fibrosis (38). On the other hand, TGFb1 has been reported to show direct positive regulation (39,40) and indirect negative regulation on the PEDF expression (41), depending on the cell environment and cell type used in the studies. It is possible that SERPINF2 rs2070863 leads to a decreased expression of a-2-antiplasmin and hence a reduction in TGFb1 production, thereby resulting in reduced TGFb1induced PEDF expression.…”
Section: Discussionmentioning
confidence: 99%